Генезис дендрофлори Волинi (антропогеновий перiод) - Oleshko, V.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
The basic stages of development of Volyn dendroflora in anthropogenic period according to literary data are given.